Integrasi Sampah Rumah Tangga menjadi POC Dukung Ketahanan Pangan Keluarga dan Zero Waste Desa Pontang - Mardiyanti, Een (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Household waste issues, particularly organic waste, along with the suboptimal utilization of home gardens, remain significant challenges in supporting household food security in rural areas. This community service activity aimed to integrate the utilization of household waste into liquid organic fertilizer (LOF) and apply it to home-garden vegetable cultivation as an effort to support household food security and implement the zero-waste concept in Pontang Village. The activity employed a participatory approach through the collection of household waste over a 20-day period from partner households, waste segregation and weighing, processing organic waste into LOF, and applying the LOF to the cultivation of short-cycle vegetables such as water spinach (Ipomoea aquatica), spinach (Amaranthus spp.), and caisim (Brassica juncea) in home gardens. The results indicated that, quantitatively, approximately 44.58% of the total household waste generated had the potential to be processed into liquid organic fertilizer, thereby contributing to the reduction of household waste generation. However, home-garden management did not fully achieve the targeted harvest due to constraints related to seed quality, pest attacks, high rainfall, waterlogging, and limited knowledge of garden managers. Nevertheless, the successful harvest achieved in several home gardens demonstrates the potential effectiveness of LOF as an organic fertilizer when supported by appropriate cultivation practices. This activity highlights that the integration of waste management and home-garden utilization requires continuous assistance, the selection of adaptive seed varieties, and strengthening community capacity to sustainably support household food security.